2021
DOI: 10.1007/s11056-021-09879-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drought and salt stress on the growth of young Populus nigra ‘Italica’ plants and associated mycorrhizal fungi and non-mycorrhizal fungal endophytes

Abstract: Populus nigra ‘Italica’ (Lombardy poplar) is a breeding cultivar of black poplar, widely used as a street tree or windbreak, often exposed to salinity and limited water availability. Populus roots can develop dual mycorrhizal associations with ectomycorrhizal (ECM) and arbuscular mycorrhizal (AM) fungi, and with non-mycorrhizal fungal endophytes (FE). The symbiotic fungi may alleviate the effects of adverse environmental conditions. We investigated the performance (growth and symbiotic associations) of one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In the same way, proline content was measured. It is well known that proline is the major osmolyte, which plays an important role in maintaining the osmotic balance of the cell during various stresses, and different mycorrhizae boost the immune system of the plants by enhancing the level of proline in both unstressed and stressed conditions (Ortiz et al, 2015 ; Kulczyk-Skrzeszewska and Kieliszewska-Rokicka, 2022 ; Zahedi et al, 2022 ). Here, after treatment with mycorrhizae, it was found that proline concentration was increasing with the increasing mycorrhizal combination.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, proline content was measured. It is well known that proline is the major osmolyte, which plays an important role in maintaining the osmotic balance of the cell during various stresses, and different mycorrhizae boost the immune system of the plants by enhancing the level of proline in both unstressed and stressed conditions (Ortiz et al, 2015 ; Kulczyk-Skrzeszewska and Kieliszewska-Rokicka, 2022 ; Zahedi et al, 2022 ). Here, after treatment with mycorrhizae, it was found that proline concentration was increasing with the increasing mycorrhizal combination.…”
Section: Resultsmentioning
confidence: 99%
“…AMF primarily alleviated the adverse effects of salt stress on AMF-inoculated Zelkova serrata seedlings by reducing Na + content, increasing P, K + , and Mg 2+ concentrations, and enhancing leaves’ photosynthetic levels and biomass accumulation [ 18 ]. The dual mycorrhizal association with ectomycorrhizal fungi (ECM), arbuscular mycorrhizal fungi, and non-mycorrhizal endophytes (FE) enhances poplar stress resistance [ 19 ]. It is important to note that ECM dominates in more mature trees, whereas AMF is present throughout the growth stages of poplar, especially at the seedling stage [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that this interaction is closely related to mycorrhizal helper bacteria (MHB). Mycorrhizal helper microorganism is a kind of special rhizosphere and endophyte that can specifically bind to mycorrhizal fungi, promote mycorrhizal fungi infection to the host, and promote plant growth and development [7,8]. The interaction of mycorrhizal fungi and auxiliary microorganisms can promote plant growth, reduce the occurrence of soil-borne diseases, and improve the availability of nutrients in soil and plant absorption rate [9][10][11].…”
Section: Introductionmentioning
confidence: 99%